Lifestyle modifications for non‐alcohol related fatty liver disease: a network meta‐analysis - Gurusamy, Kurinchi Selvan (Cochrane Database Syst Rev, 2018)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the comparative benefits and harms of different lifestyle interventions in the treatment of non‐alcohol related fatty liver disease.